"We are Rodrigo Duterte": Dimensions of the Philippine Populist Publics' Vote. Issue 3 (21st August 2019) - Arguelles, Cleve V.
Abstract : Populism is about populist publics as much as it is about populist leaders. Presently, they are pejoratively represented in public and academic conversations. Populist voting is mostly approached as a social pathology, especially in mainstream populism studies. This study is a contribution to the emerging tradition of extending empathetic approaches to the study of populist publics by interrogating how populist supporters make sense of their votes and politics through their own perspectives. Using a year‐long political ethnography of supporters of populist Philippine president Rodrigo Roa Duterte in a big slum community in Metro Manila, this research offers an intimate understanding of the electoral motivations of those who voted for him. Specifically, their vote for the populist Duterte is about making their everyday misery visible, bringing authenticity to politics, and overcoming bureaucratic inertia. Empirical observations in the field reveal the unique threefold representational, experiential, and action‐oriented dimensions of populist publics' vote in the Philippines. Abstract : "我们都是罗德里戈·杜特尔特"：菲律宾民粹主义大众投票的不同层面: 民粹主义与民粹主义大众、民粹主义领导者的相关度是一样的。目前公共交流和学术交流中对这二者的表述都含有贬义。民粹主义投票基本被视为一种社会病态，这在主流民粹主义研究中尤为明显。本文通过质疑民粹主义支持者如何从各自视角理解投票和政治，对在民粹主义研究中添加移情措施这一新兴传统做出了贡献。通过使用一项持续一年的，针对菲律宾民粹主义总统罗德里戈·罗亚·杜特尔特（Rodrigo Roa Duterte）支持者（来自大马尼拉市中的一个大型贫民窟社区）的政治民族志研究，本文深入理解了那些为杜特尔特投票的选民动机。特别地，选民为民粹主义者杜特尔特投票是希望让自己的每日遭遇得到关注，让政治回归真实，让官僚惰性得以克服。实证观察结果显示了菲律宾民粹主义公众投票的三个独特方面：代表性，经验性和以行动为导向。 Abstract : "Somos Rodrigo Duterte": Dimensiones de las Filipinas. Voto de los públicos populistas: El populismo se trata tanto de públicos populistas como de líderes populistas. Actualmente, están representados peyorativamente en conversaciones públicas y académicas. La votación populista se considera principalmente como una patología social, especialmente en los estudios de populismo general. Este estudio es una contribución a la tradición emergente de extender los enfoques empáticos al estudio de los públicos populistas al interrogar cómo los partidarios populistas dan sentido a sus votos y políticas a través de sus propias perspectivas. Esta investigación ofrece una comprensión íntima de las motivaciones electorales de quienes votaron por él. Específicamente, su voto por el populista Duterte consiste en hacer visible su miseria cotidiana, llevar la autenticidad a la política y superar la inercia burocrática. Las observaciones empíricas en el campo revelan las tres dimensiones singulares de representación, experiencia y orientación a la acción del voto del público populista en Filipinas.